(untitled) (Latakia University Journal -Medical Sciences Series, 2018)
تهدف الدراسة إلى التعرف على مستوى فاعلية الاتصال الذي يمارسه الإداريين في المؤسسات الرياضية في الجمهورية العربية السورية, حيث استخدمت الباحثة المنهج الوصفي بالأسلوب المسحي لملائمته أغراض البحث وتم إجراء الدراسة على عينة قوامها (102) من الإداريين في الاتحاد الرياضي العام وفروعه وأندية الدرجة الأولى وتم اختيارهم بالطريقة العشوائية من مجتمع البحث الأصلي. وقد أظهرت نتائج الدراسة أن مكونات الاتصال (المرسل, الرسالة, المستقبل) منسجمة مع بعضها ولا يوجد تفاوت بينها مما يخدم هدف الاتصال كعملية إدارية, وكانت درجة الاتصال متوسطة لدى العاملين في المجال الرياضي في الجمهورية العربية السورية, وكان إدراك العاملين جيد للاتصال كضرورة في فهم العمل وتحقيق أهدافه من خلال فهم معنى التوازن بين مكونات الاتصال. وأوصت الباحثة بضرورة الاهتمام بالاتصال كعملية إدارية أسوةً بالعمليات الأخرى, كالتخطيط والتنظيم والمتابعة من قبل القادة الإداريين, والتأكيد على الاهتمام التفصيلي بمكونات الاتصال لتحقيق هدفه وعدم التركيز على مكون دون الآخر, والاهتمام بالتعرف على ردود الفعل الناتجة عن عملية الاتصال من أجل التعرف على مدى تحقيق الأهداف منه, والعمل على إعداد برامج تنمية مهارات الاتصال لدى القادة الإداريين والعاملين في المجال الرياضي. The study aimed at identifying the level of communication effectiveness practiced by administrators in sports institutions in the Syrian Arab Republic. The researcher used the descriptive method in the survey method to fit the research purposes. The study was conducted on a sample of 102 managers in the General Sports Federation, In a random way from the original search community. The results of the study showed that the communication components "transmitter, message, receiver" are consistent with each other and there is no difference between them which serves the goal of communication as an administrative process. The communication level was medium among the sports workers in the Syrian Arab Republic. Work and achieve its objectives by understanding the meaning of balance between communication components. The researcher recommended that the importance of communication as an administrative process like other processes, such as planning, organization and follow-up by the administrative leaders, and emphasis on detailed attention to the components of communication to achieve its goal and not focus on the component without the other, and attention to identify the reactions resulting from the process of communication in order to identify the extent of achieving goals And to develop communication skills development programs among the administrative leaders and the sports workers.